PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUASAN PELANGGAN VILLAGE FUTSAL MEDAN - Azwardy, Luthfi; Lubis, Adelina (JURNAL PLANS, 2018)
This study aims to determine and prove whether the brand image and price of customer satisfaction Village Futsal Medan. Types This study is an associative questioning the relationship between two variables. Data analysis technique using multiple linear analysis with hypothesis test using t test, f test and coefficient of determination. The results of the discussion and conclusion indicate that incentives and motivation partially and siimultan have positive and significant influence to customer satisfaction of Village Futsal Medan.Â Keywords: Brand Image, Price, Customer Satisfaction